Optical Coherence Tomography Angiography Macular Vascular Density Measurements and the Central 10-2 Visual Field in Glaucoma. Issue 6 (June 2018) - Penteado, Rafaella C.; Zangwill, Linda M.; Daga, Fábio B.; Saunders, Luke J.; Manalastas, Patricia I.C.; Shoji, Takuhei; Akagi, Tadamichi; Christopher, Mark; Yarmohammadi, Adeleh; Moghimi, Sasan; Weinreb, Robert N.
Abstract : Purpose: To evaluate the association between macula vascular density assessed by optical coherence tomography angiography (OCT-A) and central visual field (VF) threshold sensitivities in healthy, glaucoma suspect, and glaucoma patients. Methods: A total of 185 eyes from 38 healthy participants, 31 glaucoma suspects, 72 mild glaucoma patients, and 44 moderate/severe glaucoma patients from the Diagnostic Innovations in Glaucoma Study who underwent OCT-A images of the macula and 10-2 VF testing were enrolled in this observational cross-sectional study. The relationship between central VF mean sensitivity (MS) and superficial macula whole-image vessel density (wiVD), and the relationship between the MS of the 4 central points of the 10-2 VF (MS4) and parafoveal vessel density (pfVD), were assessed using linear regression models. Results: Mean wiVD (52.5%, 49.8%, 49.4% and 45.2%, respectively) and mean pfVD (54.9%, 52.1%, 51.8% and 47.7%, respectively) were found to be significantly higher in healthy eyes and glaucoma suspect eyes compared with glaucoma eyes with mild and moderate/severe disease [analysis of covariance (ANCOVA) P <0.001]. The univariate associations between 10-2 MS and wiVD ( R 2 =26.9%) and between 10-2 MS4 and pfVD ( R 2 =16.8%) were statistically significant ( P <0.001 for both). After adjusting for scan quality, age, sex and intraocular pressure, superficial macula wiVD and pfVD were still independently associated with central VF loss. Macula wiVD performed better [area under the receiver operator characteristic (AUROC)=0.70] than ganglion cell complex thickness (AUROC=0.50) for differentiating between glaucoma suspect and healthy eyes ( P =0.010). Conclusions: Loss of OCT-A macula vessel density is associated with central 10-2 VF defects. Macula vessel density is a clinically relevant parameter that may enhance monitoring of glaucoma suspects and patients.